Bio‐based Eucommia ulmoides gum/low density polyethylene shape memory composites reinforced by zinc methacrylate. Issue 12 (10th June 2021) - Wang, Yan; Pei, Xianqiang; Xia, Lin; Zhang, Zhancheng; Wang, Qihua; Wang, Tingmei
Abstract: In this paper, we present an efficient and green extraction process for Eucommia ulmoides gum (EUG) to solve the tricky problems in separation and precipitation, providing a new idea for the industrialization of EUG extraction. Subsequently, the obtained EUG was blended with low density polyethylene (LDPE) and zinc methacrylate (ZDMA) to fabricate novel shape memory composites with both covalent and ionic crosslinking networks. It was found that the improvement in mechanical performance and enhancement in shape recovery ability of the EUG/LDPE/ZDMA composites was attributable to the Zn 2+ ‐based ionic crosslinks. The EUG/LDPE/ZDMA shape memory composites could be candidates in the production of medical fixing materials, hot‐shrinkable tubes and packaging products. © 2021 Society of Chemical Industry Abstract : Novel bio‐based shape memory materials based on natural Eucomia ulmoides gum with improved shape recovery capacity and mechanical performance were developed by introducing ionic crosslinkages.